The effect of intelligence self-control program on the quality of life of the adolescents with type I diabetes - Zinat Mohammadi; Tayebeh Mehrabi; Soheila Jafari-Mianaei (Wolters Kluwer Medknow Publications, 2020)
Background: Diabetes affects patients' quality of life in almost all physical, mental, and social areas. The aim of the present study was to determine the effect of self-control intelligence program on the dimensions of quality of life in the adolescents with diabetes. Materials and Methods: The present study is a randomized controlled trial with pre-test and post-test design in which 56 adolescents with diabetes referring to the Janan charity diabetic association in Najafabad in 2018 (Isfahan, Iran) were selected by convenience sampling method and were randomly divided into two groups of intervention (n = 28) and control (n = 28). Self-control intelligence program was performed for the intervention group. The data were collected using standard Quality of Life Questionnaire for adolescents with diabetes and were analyzed using Chi-square test, independent and dependent t-test, Mann-Whitney. Results: Statistical tests showed no significant difference between the groups in terms of their demographic characteristics such as gender, duration of diabetes, and the number of insulin injections. There was, however, a significant difference in the mean scores of all quality of life dimensions except for the dimension of physical symptoms both before and after the intervention in the intervention group (t23 = 4.46, p < 0.001). By contrast, no significant difference was observed in the mean scores of quality of life before and after the intervention in the control group (t24 = 0.08, p = 0.93). Conclusions: Based on the results, self-control program can have an effective role in the adoption of coping strategies and, thus, improves the patients' quality of life.